Analisis Yuridis Sistem Pembuktian, Beban Pembuktian, Alat Bukti dalam Undang-Undang Nomor 15 Tahun 2003 Tentang Tindak Pidana Terorisme - Dika Pranata (HUMANIORUM, 2023)
As a lex specialis, Law Number 15 of 2003 has formal specificity compared to the Criminal Procedure Code. One of these specificities that is the focus of this writing is related to the use of evidence which is a renewal of the conventional proof process in the Criminal Procedure Code. The arrangement regarding evidence in Law Number 15 of 2003 can be seen in Article 27. How is the system of proof, burden of proof, evidence in Law Number 15 of 2003 concerning Criminal Acts of Terrorism? The type of research used is normative juridical. The results of the study show that in the process of proving there are three main things, namely the system of proof, the burden of proof, and evidence. In the settlement process for criminal acts of terrorism, evidence is closely related to Human Rights (HAM). To prove whether a person is involved or not in a criminal act of terrorism, the evidentiary process plays a very important role, considering that many punishments in Law Number 15 of 2003 are in the form of life sentences or death sentences which are actually contrary to human rights. The crime of terrorism is included in the type of extraordinary crime. In terms of proof, the burden of proof is the ordinary burden of proof according to Law Number 15 of 2003